1995
DOI: 10.1007/bf00188847
|View full text |Cite
|
Sign up to set email alerts
|

aproctous, a locus that is necessary for the development of the proctodeum in Drosophila embryos, encodes a homolog of the vertebrate Brachyury gene

Abstract: The proctodeum of the Drosophila embryo originates from the posterior end of the blastoderm and forms the hindgut. By enhancer-trap mutagenesis, using a P-element-lacZ vector, we identified a mutation that caused degeneration of the proctodeum during shortening of the germ band and named it aproctous (apro). Expression of the lacZ reporter gene, which was assumed to represent expression of the apro gene, began at the cellular blastoderm stage in a ring that encompassed about 10-15% of the egg's length (EL) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 29 publications
0
26
0
1
Order By: Relevance
“…Mutant alleles used (the strongest available) were: upd os1A (a deletion) (Ferrus et al, 1990); hop C111 (Perrimon and Mahowald, 1986); Stat92E 06346 (Hou et al, 1996); drm 3 , drm 6 and drm P1 (a deletion) (Green et al, 2002); byn apro (Murakami et al, 1995); bowl 1 (Wang and Coulter, 1996); lin 2 (Hatini et al, 2000); wg 7L74 (Tearle and Nusslein-Volhard, 1987); and twi 1 (Nusslein-Volhard et al, 1984). For temperature shift experiments, the temperature-sensitive allele wg IL114 (Nusslein-Volhard et al, 1984) was used.…”
Section: Drosophila Stocksmentioning
confidence: 99%
“…Mutant alleles used (the strongest available) were: upd os1A (a deletion) (Ferrus et al, 1990); hop C111 (Perrimon and Mahowald, 1986); Stat92E 06346 (Hou et al, 1996); drm 3 , drm 6 and drm P1 (a deletion) (Green et al, 2002); byn apro (Murakami et al, 1995); bowl 1 (Wang and Coulter, 1996); lin 2 (Hatini et al, 2000); wg 7L74 (Tearle and Nusslein-Volhard, 1987); and twi 1 (Nusslein-Volhard et al, 1984). For temperature shift experiments, the temperature-sensitive allele wg IL114 (Nusslein-Volhard et al, 1984) was used.…”
Section: Drosophila Stocksmentioning
confidence: 99%
“…Strongest phenotypes, including the appearance of ectopic anal plates, were obtained when the progeny of these crosses were raised at 30°C, using at least three independent UAS-AfCad lines. The effects of AfCad mis-expression were also analysed in flies carrying Dll-lacZ (Moreno and Morata, 1999) or Byn-lacZ (Murakami et al, 1995) reporters, using the MS-248 or the apterous-GAL4 drivers.…”
Section: Drosophila Experimentsmentioning
confidence: 99%
“…Abbreviations: li, large intestine;mg, midgut;mt, Malpighian tubules;rec, rectum;si, small intestine. al., 1994;Murakami et al, 1995;Singer et al, 1996). We found that the strongest byn allele (byn apro ) does not affect drm expression in the adjacent midgut and Malpighian tubules (Fig.…”
Section: The Small Intestine Is Specified Independently Of Brachyentementioning
confidence: 99%
“…The following fly stocks are used: Oregon R as wild type for the analyzing normal development, wgPY40 (hypomorphic mutant, Murakami et al, 1994); byn apro (strongest allele, Murakami et al, 1995); srp 2 (amorphic allele; Reuter, 1994) The following GAL4 and UAS strains were used for misexpression experiments: byn-GAL4 (for misexpression in the hindgut primordium); 48Y-GAL4 (for misexpression in the midgut); maternal-GAL4 (ubiquitous); UAS-tll; UAS-wg; UAS-drm; UAS-armS10. All these strains are provided by DGRC, Kyoto Stock Center and Bloomington Stock Center, if not mentioned specifically.…”
Section: Fly Strainsmentioning
confidence: 99%
See 1 more Smart Citation